No-wait inversion—a novel model for T1 mapping from inversion recovery measurements without the waiting times - Bibiano, Juliana; Kleineisel, Jonas; Schad, Oliver; Weng, Andreas Max; Köstler, Herbert; Slawig, Anne (Frontiers in Physics, 2024)
Intro: Quantification of longitudinal relaxation time T1 became of interest as an important MRinducible tissue property for tissue characterization. Standard inversion recovery measurements for T1 determination take prohibitively long and signal models assume a perfect inversion. Acceleration is possible by employing the Look-Locker technique or other accelerated, model-based algorithms. However, the calculation of real T1 values from Look-Locker acquisitions necessitates knowledge of equilibrium magnetization M0. Thus, usually a waiting time to allow for free relaxation between global inversion pulses must be implemented. This study aims to introduce a novel model-based fitting approach for T1 mapping without the need for such waiting times. Methods: Single-inversion spiral Look-Locker FLASH acquisitions were performed in phantom and eight healthy volunteers at a 1.5T MRI scanner. The measurements comprised two parts, one without magnetization preparation and a second featuring a global inversion pulse preparation before each of the 35 slices. Acquisition was performed without any waiting time in between slices, i.e. before the inversion pulses. T1 maps were calculated based on an iterative model-based reconstruction algorithm which combines the information from these two measurements, with and without inversion. Results: Accurate T1 maps were obtained in phantom and volunteer measurements. ROI-based mean T1 values differ by an average of 1.5% in the phantom and 5% in vivo between reference measurements and the proposed method. The combined fit benefits from both the information obtained in the inversion prepared and the unprepared measurements. The former provides a large dynamic range for accurate model-based fitting of the relaxation process, while the latter provides the equilibrium magnetization M0, necessary to obtain accurate T1 values from a Look-Locker-like acquisition.The proposed model of a combined fit of an inversion-prepared and an unprepared measurement allows for robust fast T1 mapping, even in cases of imperfect inversion due to skipped waiting times for magnetization recovery. Thus, it can render long waiting times in between inversion pulses redundant.